Synaptolaemus latofasciatus, a new combination for Leporinus latofasciatus Steindachner, 1910 and its junior synonym Synaptolaemus cingulatus Myers and Fernández-Yépez, 1950 (Characiformes: Anostomidae) - Britski, Heraldo A.; Birindelli, José L. O.; Garavello, Julio C. (Zootaxa, 2011)
Leporinus latofasciatus was described by Steindachner (1910) on the basis of a single specimen collected in the río Orinoco, Venezuela. Since then, no other specimen of the species was mentioned in the literature, and the species was only listed in catalogues, eventually mentioned and treated as a “poorly known” species, or even omitted in checklists of fishes from Venezuela. During a visit to the fish collection at the Naturhistorisches Museum at Vienna (NMW) to examine all the type specimens of Leporinus, we were able to study the holotype of Leporinus latofasciatus and recognize that the specimen corresponds to the species described by Myers and Fernández-Yépez (in Myers, 1950) as Synaptolaemus cingulatus. Thus, the latter is a junior synonym of Leporinus latofasciatus and, based on that, Synaptolaemus latofasciatus (Steindachner, 1910) should be the name applied for this taxon, as a new combination. Herein new data on the holotype of Synaptolaemus latofasciatus are presented and compared with previously data from other authors. In addition, illustrations of live specimens are presented as well as new distribution records for the species.